The contribution of the ERA to the selection of the environmental indicators and to the allowance of the environmental objectives - S SAADI; M DJEBABRA (World Journal of Science,Technology and Sustainable Development, 2015)
Purpose This paper is interested to assist organizations in the task of selecting and use appropriate indicators for their environmental evaluation procedure (EPE). This maximizes the successful deployment of the EPE process and as a consequence the introduction of good environmental practices. The paper aims to discuss these issues. Design/methodology/approach It consists of a proposal for a combined methodology based on the simultaneous use of environmental risk (ER) approach and RPN-based allocation method. Findings In the developed methodology, the authors use the principles of risk assessment and purpose a new formulation of weight allowance with reference to the severity of ERs and significance of environmental aspects. Practical implications Methodology suggested constitutes an invaluable help to implementation EPE process and as a consequence the introduction of good environmental practices. Originality/value Methodology suggested facilitates the process of environmental performance evaluation providing substantial assistance to one of the most important stages that is to decide which particular indicators will be considered.